The correlation of indentation behaviour with ballistic performance for spark plasma sintered armour ceramics. Issue 8 (August 2015) - Hallam, David; Heaton, Andrew; James, Bryn; Smith, Paul; Yeomans, Julie
Abstract The Knoop and Vickers indentation behaviour of spark plasma sintered SiC–5 wt.% B4C, B4C and SiC–2.5 wt.% AlN–3 wt.% C armour ceramics have been investigated and observations correlated with ballistic performance. Surface and sub-surface indentation-induced damage has been characterised via cross-sectioning and serial ceramographic polishing techniques. The nature of the damage appears to be less influential than hardness in relation to ballistic performance, but variability in indentation behaviour appears to correlate with variability in ballistic performance. Examination of the indentation size effect curves shows that both Knoop hardness and predicted transition velocities correlate with V50 ballistic performance against an armour-piercing threat, further supporting the importance of hardness and the potential for indentation to be used as a screening method for armour materials.